THE TEACHER AS SUBJECT OF THE PEDAGOGICAL PROCESS - Jumabayeva Mahzunabonu; Jalolova Muqaddas (TADQIQOTLAR, 2025)
The article examines the multifaceted role of the teacher as the primary subject of  the  pedagogical  process.  Emphasizing  the  teacher’s  functions  beyond  the  mere transmission of knowledge, the study highlights their active involvement in organizing, managing,  and  facilitating  the  educational  environment.  The  teacher’s  professional responsibilities  are  analyzed  through  didactic,  educational,  organizational,  and communicative perspectives, reflecting the complexity of modern teaching practices. Special  attention  is  given  to  the  influence  of  the  teacher's  personality  on  students’ motivation, emotional well-being, and academic achievements. The article underscores the importance of continuous professional development, reflective practice, and the acquisition of socio-psychological competencies. In conclusion, the study reaffirms the teacher's  central  role  in  ensuring  the  effectiveness  of  the  pedagogical  process  and fostering the holistic development of learners.